PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR FARMASI DI BURSA EFEK INDONESIA - Dwi Susilowati; Chairunnisa Al Wardah; Juwari Juwari (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2022)
The purpose of this study was to determine the effect of Price Earning Ratio, Earning Per Share, Return On Equity and Debt To Equity Ratio partially on Stock Prices. In this study, a population of eleven companies and a total sample of seven pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange were taken using the criteria determined by the author. The data analysis method uses is multiple linear regression. The results of the F test are Price Earning Ratio, Earning Per Share, Return On Equity and Debt To Equity Ratio have a significant effect on stock prices in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The results of the t-test is Earning Per Share has a significant effect while Price Earning Ratio, Return On Equity and Debt To Equity Ratio have no significant effect on stock prices in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange.